The Influence of Customer Service Quality on Supply Chain Performance - Lumanga, Joseph; Muya, Francis (Journal of Industrial Engineering & Management Research, 2025)
This study assessed the influence of customer service quality on supply chain performance in logistics firms in Tanzania, focusing on the five dimensions of service quality: responsiveness, reliability, empathy, assurance, and tangibility. A correlational research design was employed to measure the relationships among these variables. Data were collected from 233 employees across Tanzania Electric Supply Company Limited (TANESCO), Simba Logistics, and Raphael Logistics using structured questionnaires based on the SERVQUAL model, with responses measured on a five-point Likert scale. Data analysis was conducted using IBM SPSS Statistics Version 27, employing both descriptive and inferential statistics. The results indicated that all five service quality dimensions had a statistically significant and positive influence on supply chain performance, with assurance and reliability demonstrating the strongest effects. The study concludes that enhancing customer service quality is crucial for improving operational efficiency, coordination, and supply chain performance. Accordingly, it recommends that logistics firms invest in regular employee training, adopt advanced technologies, maintain modern facilities, and foster professional and empathetic customer interactions to strengthen service quality and achieve sustainable supply chain competitiveness.